2018
DOI: 10.1176/appi.ps.201700107
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mental Health Courts in Reducing Recidivism: A Meta-Analysis

Abstract: Overall, a small effect of MHC participation on recidivism was noted, compared with traditional criminal processing. Findings suggest the need for research to identify additional sources of variability in the effectiveness of MHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 60 publications
(76 reference statements)
0
30
0
1
Order By: Relevance
“…36 Although MHCs across the United States vary in how participants are selected and the length of time from identification to MHC referral, they generally have the following common characteristics: voluntary participation; separate docket for defendants with mental disorders; judicial oversight of treatment plans; regular appearance by the participant in court before the judge; nonadversarial team approach with both criminal justice and MH professionals involved in the decision making, and defined conditions for successful completion. 37,38 Redlich et al 39 noted that MH courts have evolved since their first inception and describes differences between "first generation" MH courts and "second generation" MHCs. In their review, these authors note that most "first generation" courts accepted only individuals with a mental illness facing misdemeanor charges and all used sanctions when difficulties arose with compliance.…”
Section: Problem Solving Courtsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Although MHCs across the United States vary in how participants are selected and the length of time from identification to MHC referral, they generally have the following common characteristics: voluntary participation; separate docket for defendants with mental disorders; judicial oversight of treatment plans; regular appearance by the participant in court before the judge; nonadversarial team approach with both criminal justice and MH professionals involved in the decision making, and defined conditions for successful completion. 37,38 Redlich et al 39 noted that MH courts have evolved since their first inception and describes differences between "first generation" MH courts and "second generation" MHCs. In their review, these authors note that most "first generation" courts accepted only individuals with a mental illness facing misdemeanor charges and all used sanctions when difficulties arose with compliance.…”
Section: Problem Solving Courtsmentioning
confidence: 99%
“…These authors concluded that participation in the MHC program had the following positive outcomes: longer time without any new criminal charges; longer time without new charges for violent crime; and decreased recidivism and violence even after graduates were no longer under the MHC supervision. 37 In their meta-analytic investigation of studies examining recidivism rate for MHC participants, Lowder et al 38 noted that participation in MHC had a small effect on recidivism compared with traditional criminal processing but appeared to be most effective at decreasing time spent in jail after exiting from MHC. These authors encouraged further research examining strategies that may improve outcomes and decrease recidivism such as more frequent status hearings and increased attention to addressing criminogenic risks and needs.…”
Section: Problem Solving Courtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The picture for juveniles is less clear, with results ranging from slightly positive to null (Stein, Homan, & DeBerard, 2015;Sullivan, Blair, Latessa, & Sullivan, 2016;Tanner-Smith, Lipsey, & Wilson, 2016). Mental health courts have also been evaluated with some frequency, with meta-analyses showing positive outcomes (Cross, 2011;Lowder, Rade, & Desmarais, 2018;Sarteschi et al, 2011). It should be noted, however, that the meta-analyses report considerable heterogeneity in effect sizes.…”
Section: Courts In Practicementioning
confidence: 99%
“…Too morally inflected to qualify the undeserving poor for the social security disability payments and Medicaid coverage, addiction is increasingly addressed in drug courts where patient/inmates are sentenced to treatment. In a parallel process, with the surge in social security benefit applications (SSI) based on psychiatric diagnoses after passage of welfare reform and its five‐year term limits, even those with psychotic disorder diagnoses are having difficulty qualifying for benefits, and the psychotic poor are increasingly seen not in the psychiatric inpatient units that are rapidly closing, but in mental health courts that also sentence patients/inmates to outpatient treatment enforced by probation officers (Lowder, Rade, and Desmarais ).…”
Section: Capitalism and “Care”mentioning
confidence: 99%